Effect of animal feeding system information on consumer expectation and acceptability of lamb meat - Piasentier E.; Morgante M.; Saccà E.; Valusso R.; Parente J. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
One hundred and seven people took part in a central location test, organised to evaluate the consumer expectations generated by information on animal feeding system and to assess the effect of this knowledge on the hedonic ratings of local lamb meat. Using a nine-point hedonic scale, first blind and then informed scores were collected on two types of Istrian Milk meat, from lambs fed either on suckled milk and pasture (P meat) or hay and concentrate (C meat). In the blind condition, a significant difference was found between samples, C receiving higher scores than P meat (6.9 vs 6.4 points; p<0.05). There was a significant difference between expected, E, and blind, B, evaluation for both types of meat: the disconfirmation was positive for C (-0.9; p<0.01), which was perceived to be better than expected, and negative for P meat (0.9; p<0.01). Informed liking scores (I) revealed no significant differences between the two types of lamb meat and did not significantly differ from the blind hedonic scores for C meat. On the contrary, providing information on the animal feeding system positively affected the liking of P meat (I-B= 0.5; p<0.01). However this assimilation was not complete (I-E= -0.4; p<0.01), implying that both extrinsic and intrinsic characteristics have an impact on the informed liking of pasture-produced lamb meat.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)